Notch signaling and alloreactivity - Radojcic, Vedran (Transplantation, 2016)
Solid organ and allogeneic hematopoietic cell transplantation have become standard therapeutic interventions that save patient lives and improve quality of life. Our enhanced understanding of transplantation immunobiology has refined clinical management and improved outcomes. However, organ rejection and graft-versus-host disease remain major obstacles to the broader successful application of these therapeutic procedures. Notch signaling regulates multiple aspects of adaptive and innate immunity. Preclinical studies identified Notch signaling as a promising target in autoimmune diseases, as well as after allogeneic hematopoietic cell and solid organ transplantation. Notch was found to be a central regulator of alloreactivity across clinically relevant models of transplantation. Notch inhibition in T cells prevented graft-versus-host disease and organ rejection, establishing organ tolerance by skewing CD4(+) T helper polarization away from a proinflammatory response towards suppressive regulatory T cells. Notch ligand blockade also dampened alloantibody deposition and prevented chronic rejection through humoral mechanisms. Toxicities of systemic Notch blockade were observed with γ-secretase inhibitors in preclinical and early clinical trials across different indications, but they did not arise upon preclinical targeting of Delta-like Notch ligands, a strategy sufficient to confer full benefits of Notch ablation in T cell alloimmunity. As multiple clinical grade reagents have been developed to target individual Notch ligands and receptors, the benefits of Notch blockade in transplantation are calling for translation of preclinical findings into human transplantation medicine.